NUTRITIONAL STATUS OF RELATIONS WITH THE AGE OF MENARCHE IN GIRLS SMPN 3 KLATEN - Susi Wijayanti; Kuswati .; Titis Sensussiana (STIKES DUTAGAMA KLATEN, 2013)
Background: Menarche is the first menstruation are common in the age range 10-16 years or in early adolescence in the midst of puberty before entering the reproductive period. From the preliminary study found 10 girls who had experienced menarche, with good nutritional status as many as 8 students, as many as 2 schoolgirls malnutrition and nutrition are no more or obese. Objective: To determine the nutritional status of relations with the age of menarche in girls SMP Negeri 3 Klaten. Methode: Observational study used cross sectional analytic approach.This study was conducted on 23july 2013. Sample of 40 respondents used the purposive sampling technique. Correlation analysis used Spearman rank statistical test. Results: The results of this study found a significant relationship between nutritional status with age of menarche in girls SMP Negeri 3 Klaten, with the result that asymp. Sig 0.000 <0.05 (5%).Conclusion: There is a significant relationship with the nutritional status of the relationship of age of menarche in girls SMP Negeri 3 Klaten.